2010
DOI: 10.1016/j.jpainsymman.2009.11.327
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Usefulness of Peripherally Inserted Central Venous Catheters in Terminally Ill Cancer Patients

Abstract: PICCs were safely inserted in about 90% of terminally ill cancer patients within about 20 minutes. Although 30% of the patients experienced transient mild procedure-related distress, more than 90% of the patients felt that the parenteral route was more comfortable and convenient after the procedure. PICCs may provide a safe, comfortable, and convenient alternative for terminally ill cancer patients, if placement of the PICC is individualized to the patient situation and after alternatives are considered. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 19 publications
3
42
1
2
Order By: Relevance
“…These high rates of PICC self-removal can be explained by delirium, which develops in up to 80∼90% in terminally ill cancer patients (10). A Previous report that studied PICC in terminally ill cancer patients showed 10% of PICC self-removal, a value similar to that in our study (11). However, there was no serious problem after self-removal except manageable trivial bleeding.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These high rates of PICC self-removal can be explained by delirium, which develops in up to 80∼90% in terminally ill cancer patients (10). A Previous report that studied PICC in terminally ill cancer patients showed 10% of PICC self-removal, a value similar to that in our study (11). However, there was no serious problem after self-removal except manageable trivial bleeding.…”
Section: Discussionsupporting
confidence: 87%
“…However, only limited data exist regarding the safety and efficacy of PICC in terminally ill cancer patient with only 1 published study worldwide (11). In Korean, thus far, only two reports have described PICC in a general oncology setting (9,12), and no study has reported in a homogeneous cohort of terminally ill cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Este hallazgo es congruente a lo reportado por Yamada et al (2010), donde se muestra que el confort relacionado con la utilidad del PICC es alto (40).…”
Section: Discussionunclassified
“…Por otra parte, se ha observado que la inserción del PICC es un evento poco estresante para el paciente y que por el contrario, existen buenos niveles de confort asociados con la utilidad del PICC (12). Frente a esto, en la experiencia práctica en el INC, se ha evidenciado que los pacientes pediátricos no candidatos a catéter implantable y sus cuidadores, han manifestado altos niveles de estrés, dolor y ansiedad relacionados con los continuos pinchazos a los que son sometidos para la administración de quimioterapia, líquidos, transfusiones y toma de laboratorios, lo que en varias oportunidades los ha cuestionado acerca de continuar o no con el tratamiento.…”
Section: Introductionunclassified
“…Currently, peripherally inserted central venous catheters (PICCs) are frequently used for patients with advanced cancer, mainly to maintain chemotherapy, nutritional therapy, and/or for symptom control. 7,8 The subclavian or jugular venous access route and PICC may be difficult or contraindicated in some clinical situations (in patients with mediastinal masses, SVC thrombosis, or massive cutaneous metastases). In addition, subclavian or jugular vein catheterization may involve life-threatening procedure-related complications (pneumothorax, hemothorax, and arterial puncture) in terminally ill patients with cancer.…”
Section: Introductionmentioning
confidence: 99%